THE LANGUAGE PREFERENCES IN DOMAINS OF COMMUNICATION AMONG MARINDUQUEÑOS - Pineda, Susan (International Journal of Arts, Sciences and Education, 2025)
Language varieties in different speech communities exist in different groups of speakers. For example, in the province of Marinduque, it was observed that the native speakers use different kind of languages in communicating to various groups of speakers in several domains. This paper is an attempt to identify the language preferences of the speakers in different domains. These domains include the family, the school, and the church. This also analyzes the factors that influence the speakers’ choices of using one language in a particular domain. This study adopted Fishman’s (1965) theory on language use “Who speaks what language to whom and when” applies to this study. In this theory, all utterances made by the native speakers from the oral language samples are bases in claiming that they vary in their language use in situational domains like the family, the school and the church presented in a box at the lower portion of the paradigm. It is presumed that in the three categories of domains, the native speaker is likely to use the more or the most appropriate language in dealing with different categories of speakers. He/she also considers the subject matter of the social interaction and the purpose of the conversation. The results show that in different settings of conversations, the local language (Marinduque Tagalog) is preferred by the native speakers in the three domains, however, most defined in the family domain. The native speakers are more comfortable in their interaction as they find it simpler to express themselves using the local language. Standard Tagalog (Manila Tagalog) and English are used only in the church and school domains by the professionals and native speakers who are exposed to both languages. The factors identified influencing the language preferences of the speakers in the family, the school, and the church domains are the following: transfer of residence, local language area, mores and tradition, educational attainment, and language contract. Specifically, native speakers in the church domain agreed that transfer of residence, mores, and traditions, and gender influence the most the native speakers, whereas in the school domain, the enumerated significant factors are educational attainment, geographical location, and mores and traditions. It was very clear then that the native speakers are still loyal in the use of Marinduque Tagalog both in formal and informal conversations in different domains. Specifically in Western Marinduque, Marinduque Tagalog is preferably used in formal conversations particularly with lay ministers and nuns. In Eastern Marinduque, Marinduque Tagalog is also the choice of the family members and school officials including the students in both formal and informal conversations.